Perlindungan Hukum Bagi Tenaga Kerja Stasiun Kereta Api Ditinjau Melalui Pandangan Hukum Islam - Arifuddin Muda Harahap (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
Train is a land transportation service that is widely used by the community with various advantages and benefits that can be achieved. Of course PT. KAI (PERSERO) as a State-Owned Enterprise (BUMN) has a large workforce. Companies should provide good service by ensuring the rights and obligations of their workers can be realized properly. The state must also ensure legal protection for workers without exception, because the role of workers is very important in the life of the nation.Keywords: railways, labor, rights and obligations, legal protection